Information Management Database System Managerial Supervision of School Supervisors - M.Rusni Eka Putra; Marianita Marianita; Ahmad Gawdy Prananosa (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2021)
This article aimed at managing information technology based school supervisory managerial supervision database. The approach in this study uses a system approach with a waterfall model. The steps of developing the model are requirements analysis, design, implementation and unit testing, integration and system test. The results show that School supervisors in the North Musi Rawas District Office still use the manual system, and design of managerial supervisory information systems for principals are designed based on planned flowcharts. The results of expert validation, the supervisory managerial supervisory database includes; curriculum and learning administration, class administration, school administration and management, organization and institutions, facilities and infrastructure, staffing, funding, students, community participation, school cultural environment are appropriate to be used. The appropriate Implementation of the School Supervisory Managerial with Supervision Database SIM. Keywords: Management Information System, Management Supervision, System Managerial Supervision